A multifunctional TiN/Ni electrode for wearable supercapacitor and sensor with an insight into charge storage mechanism - Akbar Sial, Qadeer; Thai Duy, Le; Singh, Ranveer; Iqbal, Shahid; Yeasmin, Rubaya; Lee, Young Jae; Kalanur, Shankara S.; Seo, Hyngtak (Applied Surface Science, 2021)
Titanium nitride (TiN) recently withdraws much attention for the development of wearable electronic devices, especially energy storage and sensing devices. However, the stability of this multifunctional material is of great concern, particularly in oxidizing environments or under structural deformations during the device operation. Given this, here we innovate the TiN material with an ultrathin Ni passivation (named “TiN/Ni”) for fabrications of not only stable energy-storing supercapacitors but also high-performance temperature sensors. Importantly, the insight to structural and chemical changes during the charging and discharging of the energy device is focused and explored by using Kelvin probe force microscopy (KPFM; to directly monitor the nanoscale level structural changes, morphology, and work function of the materials). The support of Ni to the chemical stability and electro-conductivity of TiN are discussed. The specific capacitance of our TiN/Ni supercapacitor reached 10.21 mF/g at a scan rate of 5 mV/s with an energy density of 5.641 mWh/kg and a power density of 1.084 W/kg. Meanwhile, the TiN/Ni temperature sensor operated well in a temperature range of 20–100 °C with high sensitivity of 1.562%/°C (near 20 °C). Overall, these confirm the usability of our TiN/Ni in developing wearable devices.
Keywords: Charge storage; Electronics devices; Energy; Multi-functional materials; Multifunctional; Ni electrodes; Oxidizing environments; Sensing devices; Storage mechanism; Titania; Multifunctional; Nanocomposite; Supercapacitor; Temperature sensor; Titanium nitride; Wearable